Measuring the Impact of Continuous Disinfection Strategies on Environmental Burden in Outpatient Settings: A Prospective Randomized Controlled Trial. (13th September 2020) - Warren, Bobby G; Turner, Nicholas; Smith, Becky; Addison, Rachel; Marden, Samantha; Weber, David J; Rutala, William A; Anderson, Deverick J
Abstract: Background: Our primary objective was to determine the effectiveness of 2 enhanced disinfection strategies compared with standard disinfection: "near-UV" light (Arm 1) and a persistent organosilane quaternary ammonium disinfectant (Arm 2) using a triple-blind study design. Our secondary objective was to characterize environmental contamination of outpatient clinics. Methods: This trial was conducted at 2 clinics: the wound and pulmonary outpatient clinics at Duke University Health System in Durham, North Carolina. In Arm 1, room overhead lights were replaced with 405-nm near-UV visible light bulbs. In Arm 2, the organosilane quaternary ammonium disinfectant was applied to all room surfaces. The control arm received no intervention. All arms received routine disinfection. Room contamination was measured twice daily (before and after clinic) over 25 clinic days. Results: The primary outcome was the change in total contamination, measured in colony forming units (CFUs), on environmental surfaces at the end of the clinic day compared with the beginning of the clinic day. Results from each intervention arm were compared against results from the control arm. The median delta total CFU for Arm 1 was 2092 CFUs (interquartile range [IQR], −1815 to 8566); the median delta for Arm 2 was 2016 CFUs (IQR, −1443 to 7430). Compared with the control arm (median delta = 1987 [IQR, −1611 to 15 857]), neither intervention led to a significant decrease in daily room contamination change ( P for Arm 1 = 0.78 and P for Arm 2 = 0.71). Conclusions: Neither near-UV lights or a persistent organosilane quaternary ammonium disinfectant reduced environmental contamination in 2 outpatient clinics compared with control rooms but did reduce the number of clinically important pathogens recovered.